Critical Analysis and Problem-Solving Performance in Trigonometry Among College Students - Christine Joy L. Sosa; Rosebelle Diane T. Ilagan; Leah M. Lavarite; Lovely Angel A. Polianario; Joane F. Santiago; Zussette Candelario - Aplaon (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Problem-solving is believed to be the essence of mathematics learning. Problem-solving in Trigonometry is crucial for developing critical thinking and analytical skills, spatial reasoning, and a strong foundation for advanced mathematics. It also has practical applications in various fields, making understanding the factors influencing problem-solving skills essential. This study aims to investigate the specific role of critical thinking in trigonometry problem-solving performance. This study determined the critical analysis of mathematical translation and identifying appropriate formulas. On the other hand, the problem-solving performance was measured in terms of Polya’s framework, which included understanding the problem, devising a plan, carrying out a plan, and looking back. The study utilized a Descriptive-correlation research design to determine the significant relationship between the two variables. A summative test was used as the data-gathering tool to assess the participants' performance. The study participants were thirty-four (34) randomly selected college students at a particular state university in Oriental Mindoro. The data were analyzed using Mean, frequency-percentage, and Pearson’s r. The study's results revealed a significant relationship between the level of critical analysis and the level of performance in Trigonometry.